Pengaruh bising lingkungan sekolah terhadap kelelahan bersuara pada guru sekolah dasar - Hellena Miranda; Abdul Rachman Saragih; Adlin Adnan; Tengku Siti Hajar Haryuna (PERHATI-KL, 2011)
Background: The effect of noisy school environment is not only affecting student’s consentration level, but also causing problem to teachers’s voice. Purpose: To know the influence of noisy school environment techers voice intensity of the lecturer toward the lecturer’s speaking exhaustion at a number of elementary school located in Medan. Method: The research used case control method upon 90 elementary school teachers as the subject. The teachers came from schools influenced by noisy environment and schools with quite environment located in the city of Medan. The exhaustion level of speaking is identified by score of voice handicap index (VHI). The statistical tests used were “t-test”, Chi-square test and the multinomial logistic regression test. Result: Average level of noise in case group was 80.8 dB, in control group was 54.6 dB, with voice intensity of 79.6 dB and 61 dB. The voice disturbance in both group identified as medium level with the score of VHI ranges from 20-40 (p=0.03). By statistical analysis using “Xtest”, we found significant corelations between the VHI score with school noise (p=0.03), the lecturer’s voice (p=0.03) and sex (p=0.01). The result of multinomial logistic regression test shows that voice exhaustion disruption were influenced by school noise intensity (OR=3.4, IK95%=1.05-10.94) and the lecturer’s voice intensity (OR=3.2, IK95%=1.04-10.07).Conclusion: Teachers at schools with noisy environment had 3.4 times higher risk than teachers from schools with quite environment, and teachers who used high intensity voice had 3.2 times higher risk than teachers with low intensity for voice disturbance. Key words: voice exhaustion, noise intensity, voice intensity Abstrak : Latar belakang: Lingkungan sekolah yang bising selain mempengaruhi konsentrasi belajar-mengajar, dapat juga menyebabkan masalah bersuara pada guru. Tujuan: Untuk mengetahui pengaruh bising lingkungan sekolah dan intensitas suara mengajar terhadap kelelahan bersuara pada guru di beberapa sekolah dasar negeri di kota Medan. Metode: Desain penelitian ini adalah studi kasus kontrol dengan subjek penelitian 90 guru yang mengajar di sekolah yang terpajan bising dan sekolah yang tidak terpajan bising di kota Medan. Tingkat kelelahan bersuara diidentifikasi melalui skor voice handicap index (VHI). Uji statistik yang digunakan uji t, uji X dan uji regresilogistic multinomial. Hasil: Rerata intensitas bising pada kelompok kasus sebesar 80,8 dB, sedangkan pada kelompok kontrol sebesar 54,6 dB. Intensitas suara guru saat mengajar, masing-masing sebesar 79,6 dB dan 61 dB. Gangguan kelelahan bersuara pada kedua kelompok tergolong ringan, dengan skor VHI sebesar 20-40 untuk kedua kelompok (p=0,03). Setelah dilakukan analisis statistik terhadap variabel yang diduga mempengaruhi skor VHI dengan menggunakan uji X2didapatkan hubungan yang bermakna antara intensitas bising sekolah (p=0,03) intensitas suara guru (p=0,03) dan jenis kelamin (p=0,01) dengan skor VHI. Hasil uji regresi logistik multinomial menunjukkan bahwa hanya intensitas bising sekolah (OR=3,4, IK95%= 1,05-10,94) dan intensitas suara guru (OR=3,2, IK95%=1,04-10,07) berpengaruh terhadap gangguan kelelahan bersuara.Kesimpulan: Guru yang mengajar di sekolah yang terpapar bising memiliki risiko kelelahan bersuara 3,4 kali lebih tinggi dibandingkan dengan guru di sekolah yang tidak terpapar bising, dan guru dengan intensitas suara yang tinggi saat mengajar akan mengalami kelelahan bersuara 3,2 kali lebih sering dibandingkan guru dengan intensitas suara rendah. Kata kunci: kelelahan bersuara, intensitas bising, intensitas suara